O livro de Daniel em oposição ao epicurismo : a relação entre a literatura apocalíptica judaica e a filosofia helenística no séc. II a.E.C. - Santana, Thiago Borges de (2018)
The expansion of the ancient Kingdom of Macedonia, under the leadership of Alexander The Great, prompted the accession of Hellenic cultural dimensions throughout the West and Middle East in a process of cultural diffusion known as Hellenization. However, hellenistic cultural dominance was not without struggle Thus, this research has proposed as an hypothesis that the Old Testament book of Daniel is a result of a socio-religious experience that countered epicureanism by highlighting the principle of faithfulness to Yahweh. Daniel’s apocalypse offers a conception that the Jewish monotheistic deity interferes history in a conclusive manner, since in the end of time it will be judging all of the infidels (Dan 7: 13-14). Such philosophical system believed that the gods were in a state of ataraxia, blissfulness, serenity, antipathetic to any human feeling. Therefore, from a cultural approach of the religious phenomenon it has been scrutinized if the book of Daniel, written in an apocalyptic language, presents a proposal of socio-religious way of life posing an antithesis to the Epicurean doctrine while fostering the maintenance of a Jewish identity related to the divine figure of Yahweh in the second century BCE.